Rate of Cesarean Delivery among Physicians Practicing in A Teaching Hospital in Tigray Region, Northern Ethiopia - Teka, Hale; Yemane, Awol; Ahmed, Sumeya; Berhe, Ephrem; Gebremeskel, Mebrihit; Ebuy Abraha, Hiluf; Hasan, Abida; Abate, Ermias (Ethiopian Journal of Reproductive Health, 2023)
Abstract Introduction: The Ethiopian national cesarean section rate is about 5%. Rates of cesarean delivery (CD) vary widely among population segments in Ethiopia suggesting unequal access. Within this context, this study aimed to assess the rate of CD among physicians practicing at Ayder Comprehensive Specialized Hospital (ACSH). Methods: This was cross-sectional study. All female physicians who are parous (n = 15) and all male physicians whose spouses are parous (n = 86) were interviewed to evaluate the mode of delivery among them. Indications for CD were also assessed. Results: The overall CD rate among participants was 81 (44.3%). Thirteen out of 18 (87%) female obstetrician/gynecologists and male obstetrician/gynecologists’ spouses delivered via CD. Cesarean delivery for maternal request (CDMR) accounted for 22.6% of primary CDs. Nearly all (95%) potential candidates for Trial of Labor after Cesarean delivery (TOLAC) opted for repeat elective CD. The driving factors for CD were: lack of confidence in the process of intrapartum fetal monitoring, “uncertainty” of outcome of vaginal delivery, fear of labor pain (due to absence of labor analgesia), and managing obstetricians’ fear of blame for poor outcome by their colleagues. Conclusion: This study revealed a disparity in CD rates in physician community vs the general Ethiopian population. More revealing are the reasons why they underwent CD. Rate of CD may be decreased by winning the confidence of the parturient mothers through instituting international-standard intrapartum fetal monitoring and labor analgesia protocols. Key Words Mode of delivery, Cesarean delivery, maternal request, physicians